TECHNOLOGY ADAPTATION AND ITS IMPACT ON E-LEARNING IMPLEMENTATION AT THE STATE ISLAMIC UNIVERSITY OF PALEMBANG CITY - FERA INDASARI; Gita Astrid; Safitri Elfandari (Ath Thariq Jurnal Dakwah dan Komunikasi, 2025)
The rapid advancement of technology has significantly influenced the educational landscape, necessitating the adaptation of e-learning systems in higher education institutions. This study aims to explore the processes and outcomes of technology adaptation in implementing e-learning at the State Islamic University. The research focuses on identifying the key factors that facilitate or hinder the adoption of e-learning technologies, evaluating the effectiveness of these technologies in enhancing educational delivery and assessing the overall impact on students and faculty. The study employs a descriptive qualitative method, involving interviews with lecturers and students to gather comprehensive insights into their experiences and perceptions regarding e-learning adaptation. The findings reveal that the successful adaptation of e-learning technologies heavily depends on institutional support, technological infrastructure, and user competence. Additionally, the results indicate a positive correlation between e-learning implementation and improved academic performance, student engagement, and teaching efficiency Despite these benefits, challenges such as resistance to change, technical issues, and the digital divide among students remain significant barriers.  By addressing these issues, the State Islamic University can enhance its e-learning capabilities, providing a more flexible, efficient, and inclusive educational environment for all stakeholders.